Nilai-Nilai Akhlak dalam Surah Luqman Ayat 14-15 Perspektif Tafsir Al-Mishbah dan Relevansinya dengan Pembentukan Karakter Remaja (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to analyze in depth the moral values ​​contained in Surah Luqman verses 14–15 based on M. Quraish Shihab's Tafsir Al-Mishbah and their relevance in shaping the character of adolescents in the modern era. The research method used is library research with the tafsir munasabah approach, namely examining the relationship between the meanings of verses contextually and thematically. The main data source comes from Tafsir Al-Mishbah, supported by relevant tafsir literature and character education studies. The results of the study show that in Tafsir Al-Mishbah, Surah Luqman verses 14–15 contain six main moral values, namely birrul wâlidayn (devotion to parents), an attitude of gratitude to Allah and both parents, proportional obedience and not violating the principle of monotheism, gentleness and ethics in responding to differences, orientation to the afterlife, and exemplary behavior. These values ​​have strong relevance to efforts to shape the character of adolescents, especially in facing moral challenges in the digital era. The implementation of this teaching is considered strategic as a fundamental solution to overcome various youth problems, such as cyberbullying, ethical crises, and moral decadence, by instilling religious attitudes, empathy, and social responsibility.